Thermofield Cr→Cr²⁺ recharging resulting in anomalous intensification of Cr²⁺ emission in ZnS:Cr thin-film electroluminescent structures - Vlasenko, N.A.; Oleksenko, P.F.; Denisova, Z.L.; Mukhlyo, M.A.; Veligura, L.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
For the first time, an anomalous strong increase of the Cr²⁺ emission intensity
(I) with increasing the applied voltage (V) has been discovered in ZnS:Cr thin-film
electroluminescent structures (TFELS) instead of the I(V) dependence saturation typical
of TFELS of the MISIM type, where M is an electrode, I is an insulator layer and S is an
EL film. The dependence of I on the transferred charge (Q) is very superlinear, whereas
the luminance of the emission of hot electrons, which takes place simultaneously with the
Cr²⁺ emission, increases proportionally to Q as it happens usually in TFELS. The
increase of I and Q is accompanied by rising the sample temperature up to 30 – 50 °C.
However, the emission spectrum that is inherent to the ⁵E → ⁵T₂ transition in the 3d shell
of a Cr²⁺ ion is not changed in this case. The above effects are explained by Cr⁺ → Cr²⁺
thermofield recharging, which results in an increase of the number not only of free
electrons, but also of Cr²⁺ radiation centers. The most probable mechanism of such a
recharging is the Frenkel-Pool field-stimulated thermal ionization of Cr⁺
ions, whose ionization energy is 0.65…0.82 eV.